PROBLEMATIKA PEMAHAMAN METODOLOGI KUANTITATIF: TANTANGAN PEMBELAJARAN KOMPREHENSIF DI PERGURUAN TINGGI - Nurrohmah; Jaelani, Misnan; Husin, Fuad; Kusnan; Sobirin (STKIP Subang, 2026)
Research is a scientific activity conducted systematically and in a planned manner to acquire new knowledge and to address various problems in society. This study aims to analyze students' understanding of quantitative research methodology within higher education learning contexts. The research employs a library research approach by reviewing various relevant scientific literature, including journals, books, and academic articles. The findings indicate that students' understanding of quantitative research tends to be limited to technical aspects, such as numerical data processing and statistical analysis, while their comprehension of conceptual, methodological, and philosophical foundations remains insufficient. Furthermore, students demonstrate a low level of understanding regarding the tradition of quantitative research, particularly its grounding in the positivism paradigm. Misconceptions are also found in fundamental concepts such as variables, hypotheses, and research design. Overall, students’ understanding is categorized as moderate and requires further improvement. These findings suggest the need for more comprehensive and integrative learning strategies in teaching research methodology, emphasizing not only procedural skills but also conceptual and philosophical understanding.